Amyotrophic lateral sclerosis (ALS) health charities are central to ALS care: perspectives of Canadians affected by ALS. Issue 3 (3rd April 2023) - Ahmad, Mira; Genuis, Shelagh K.; Luth, Westerly; Bubela, Tania; Johnston, Wendy S.
Abstract: Objective: Expert consensus guidelines recommend referral of people with amyotrophic lateral sclerosis (ALS) to ALS health charities for support. Limited research indicates that patients and families value interaction with these volunteer sector organizations. We investigated how patient support from Canadian ALS health charities (ALS Societies) is experienced by those affected by ALS, and whether patient-centered outcomes validate recommendations for referral. Methods: Data were drawn from the ALS Talk Project, an asynchronous online focus group study. Patients and family caregivers were recruited from regions across Canada. Seven groups met online for 14 weeks between January and July 2020. Seventy-eight participants made statements about ALS Societies. Data were qualitatively analyzed using directed content analysis and the constant-comparative approach. Results: Participants viewed ALS Societies as integral to the healthcare system. The Societies acted as patient navigators and filled perceived care gaps, including psychological support. They provided critical practical assistance, particularly equipment loans and peer support groups; comprehensive disease-related and real-life information; and personal connections. They facilitated knowledge of research, emerging therapies, and research opportunities. Delayed referral to ALS Society supports and information resources was a concern for some participants. Conclusions: ALS Societies provide patients with critical practical, informational, and emotional support and play an overarching role as patient/research navigators. Patient-centred outcomes support patient referral to ALS Societies. Communication about the services provided should be a standard component of clinical care, with choice of access left to individuals. Clinical conversations should be supplemented with information resources developed by these voluntary sector organizations.